Reduced H3K27me3 and DNA hypomethylation are major drivers of gene expression in K27M mutant pediatric high-grade gliomas - Bender, Sebastian; Tang, Yujie; Lindroth, Anders; Hovestadt, Volker; Jones, David T. W.; Kool, Marcel; Zapatka, Marc; Northcott, Paul A.; Sturm, Dominik; Wei, Wang; Radlwimmer, Bernhard; Højfeldt, Jonas W.; et al. (Cancer cell, 2013)
Two recurrent mutations, K27M and G34R/V, within histone variant H3.3 were recently identified in ∼50% of pHGGs. Both mutations define clinically and biologically distinct subgroups of pHGGs. Here, we provide further insight about the dominant-negative effect of K27M mutant H3.3, leading to a global reduction of the repressive histone mark H3K27me3. We demonstrate that this is caused by aberrant recruitment of the PRC2 complex to K27M mutant H3.3 and enzymatic inhibition of the H3K27me3-establishing methyltransferase EZH2. By performing chromatin immunoprecipitation followed by next-generation sequencing and whole-genome bisulfite sequencing in primary pHGGs, we show that reduced H3K27me3 levels and DNA hypomethylation act in concert to activate gene expression in K27M mutant pHGGs.